EFFECT OF COMMITMENT ORGANIZATION, ORGANIZATIONAL CULTURE, AND MOTIVATION TO PERFORMANCE OF EMPLOYEES - Anggapradja, Indra Taruna; Wijaya, Ronny (Universitas Brawijaya, Indonesia, 2017)
This study aims to determine the influence of organizational commitment, organizational culture, and motivation on employee performance of employees at PT. INTI. The research question in this study is how the influence of organizational commitment, organizational culture, and motivation to employees performance at PT. INTI. This study uses a quantitative approach. This research data source of primary data. Primary data were obtained using a questionnaire addressed to employees of PT. INTI. Respondents of this study are employees of PT. INTI whose number is 78 people. The conclusion of this study that variable organizational commitment, organizational culture, and motivation positive and significant impact on the performance of employees of PT. INTI.